School exclusion : research themes and issues / Isabelle Brodie, David Berridge. - Brodie, Isabelle (University of Luton Press, 1996)
In February 1996 a two day seminar on exclusion was held at the University of Luton. The seminar gave researchers the chance to present up-to-date findings on exclusion & to relate these to policy concerns. This book reports on these findings.